2014
DOI: 10.15761/icst.1000109
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Cancer is one of the major health problems with a high mortality rate. Apart from the genetic changes in cancer cells, epigenetic and environmental factors play an important role towards the progression of tumor. The new cancer cases worldwide are estimated to increase to 19.3 million per year by 2025, due to the changing lifestyle and increase in longevity. Social and economic changes have contributed to rising risks of cancers associated with dietary and hormonal factors. Although traditional therapies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Small molecule inhibitors are compounds (<500 Da) able to penetrate tissue more effectively than macromolecules and are usually suitable for oral administration [245]. Although several small molecule inhibitors have been approved for cancer treatment, it is essential to further identify new compounds, to overcome drug resistance [246].…”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%
“…Small molecule inhibitors are compounds (<500 Da) able to penetrate tissue more effectively than macromolecules and are usually suitable for oral administration [245]. Although several small molecule inhibitors have been approved for cancer treatment, it is essential to further identify new compounds, to overcome drug resistance [246].…”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%
“…138,139 The development of such methodologies for therapeutic intervention outside of enzymes and receptors could have huge benefits in medicine, with a very wide range of specific applications in cancer. 140 Other small-molecule inhibitors that target the proteasome, heat-shock proteins, matrix metalloproteinases, BH-3 mimetics (eg, venetoclax), 141 and targets such as these will continue to offer critical opportunities for the development of a diverse menu of inhibitors. 140 Although fragment-based drug design 142 and proteolysis-targeting chimera 143 technologies are not new drug discovery strategies, they are now proving fruitful for targeting oncogenic-driving proteins that were previously considered undruggable, including RAS.…”
Section: Knowledge Gap and Challengesmentioning
confidence: 99%
“…140 Other small-molecule inhibitors that target the proteasome, heat-shock proteins, matrix metalloproteinases, BH-3 mimetics (eg, venetoclax), 141 and targets such as these will continue to offer critical opportunities for the development of a diverse menu of inhibitors. 140 Although fragment-based drug design 142 and proteolysis-targeting chimera 143 technologies are not new drug discovery strategies, they are now proving fruitful for targeting oncogenic-driving proteins that were previously considered undruggable, including RAS. In contrast, although tumor suppressors, including the retinoblastoma protein, are functionally inactivated in many cancers, 144 they have thus far remained refractory to drug-targeting approaches.…”
Section: Knowledge Gap and Challengesmentioning
confidence: 99%
“…Therefore discovery of new anticancer agents through chemical structural modifications on the basis of leading compounds is a must. [43,44] Therefore, it was suggested that these enzymes may be attractive, and the use of inhibitors could provide promising results for the diagnosis and treatment of breast cancer. [25,26] Pyrimidine is a common structural skeleton now considered one of the potential scaffolds for investigation in cancer therapy, [45,46] and compounds Ic, IIc (Figure 1) are representative drugs in this class in clinical use or under investigation targeting therapies strongly connected to breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Considering these facts, new treatments for breast cancer improving survival and quality of life, together with reduced morbidity, are highly sought for new anticancer leads. [43,44] Furthermore, an inspection of the compounds illustrated in Figure 1 indicated that the nitrile group is an important pharmacophore present in a number of anticancer agents including ARIs such as letrozole (Ia) [10] and anastrozole (Ib), [11] and EGFR inhibitors such as neratinib (IId) [36] and pelitinib (IIIa) [37] for the treatment of breast cancer. [24] It has been documented that the electron-withdrawing nitrile group in Ia and Ib is liable for coordination to the heme group of ARO.…”
Section: Introductionmentioning
confidence: 99%